Perubahan Pola Perilaku Memilih Kaum Santri dalam Pemilu Daerah Serentak 2020 di Kabupaten Sumenep - Putri, Rizca (Talenta Publisher, 2023)
Sumenep as one of the regencies on Madura Island cannot be separated from the strong influence of Kiai and Pesantren (Islamic Boarding School) in it. Kiai as religious leaders and teachers not only hold a cultural role but also a political role, especially during the General Election. Candidates for regional leaders are certainly competing to get Kiai and Pesantrens to increase their winning potential. However, what is the actual position of Kiai and Pesantren in the life of an increasingly developing society. This article aims to discuss the shift in the role of Kiai in the Simultaneous Pilkada. By using a qualitative approach. Collecting data using observation, interviews, and observations. The results of the study show that the development of information, the split in support of Kiai and pesantren as well as practical transactions have made Kiai and pesantren unable to fully mobilize and influence people's political preferences in Simultaneous Regional Elections.